Investigation of Flooding due to Dam Failure: A Case Study of Darlık Dam - Ezgi Selen Tilav; Sezar Gülbaz (Doğal Afetler ve Çevre Dergisi)
Dams are engineering structures that are of great importance in regularly meeting the drinking and utility water that we need, providing electrical energy needs, protecting residential areas against floods, and creating recreation areas. Although dams have many benefits, it is known that the damages in these structures poses serious disaster risk for the settlement areas located downstream. In addition, our existing dams, which are aging, and in addition to these, our dams that are increasing day by day, increase the disaster risk even more, especially in areas with increasing residential areas downstream. In this study, Darlık Dam, which is located in Istanbul and has a dense residential area on its downstream, was selected as the study area. Dam failure simulation was developed at the downstream of Darlık Dam and the areas that would be affected by the flood wave were observed. In this context, it is aimed to contribute to the determination of the areas where measures should be taken by the authorized institutions and to the prevention or reduction of the disasters that will occur due to dam failure. Failure analyzes of Darlık dam were generated by using HEC-RAS program. In accordance with the dam breach scenario, the breach parameters were defined into the HEC-RAS program and the dam failure flood analysis was modelled in two dimensions. Within the scope of the study, flood flow, water velocity and water depth were calculated in case of possible dam failure. Flood inundation, depth and velocity maps were obtained. Flood hazard areas was created and possible flood wave’s hazard ratio was determined by observing flood inundation areas. Finally, damage of buildings in flood wave areas was calculated and damage ratio and risk maps were obtained. According to the result of damage calculation, it was observed that approximately 3043 buildings were damaged. The damage ratio was shown on the flood inundation areas. It was concluded that %80.05 of all buildings affected by the flood are in the very high risk class. In the next stage, each building in the flood inundation areas was marked according to its risk class, shown in risk maps and presented within the scope of the study.